2015
DOI: 10.1093/toxsci/kfv142
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene is a Novel Constitutive Androstane Receptor (CAR) Activator and Causes Hepatotoxicity by CAR

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a class of ubiquitous persistent environmental pollutants which are primarily formed from the incomplete combustion of organic materials. Many potential sources of human exposure to PAHs exist, including daily exposures from the ambient environment or occupational settings. PAHs have been found to cause harmful effects on human health. Here, we evaluated the adverse effects of pyrene, a common PAH, on the liver. The present study demonstrates that pyrene is able to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Elevated plasma ALT and DBIL levels observed in our study reflected rat liver injury caused by pyrene. Our previous study demonstrated that oral administration of pyrene for 4 days induced hepatotoxicity in adult male mice (C57BL/6 genetic background) at the dose of 300 mg/kg . The 300 mg/kg pyrene dose used in our previous study in mice was approximately 37.5% of the mouse LD 50 , while the 1500 mg/kg dose performed in this study was approximately 54.5% of the rat LD 50 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Elevated plasma ALT and DBIL levels observed in our study reflected rat liver injury caused by pyrene. Our previous study demonstrated that oral administration of pyrene for 4 days induced hepatotoxicity in adult male mice (C57BL/6 genetic background) at the dose of 300 mg/kg . The 300 mg/kg pyrene dose used in our previous study in mice was approximately 37.5% of the mouse LD 50 , while the 1500 mg/kg dose performed in this study was approximately 54.5% of the rat LD 50 .…”
Section: Discussionmentioning
confidence: 53%
“…Chen et al demonstrated that coke oven emissions primarily consisting of PAHs, including 25% pyrene, significantly induced serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase in coke oven workers . Our previously identified that constitutive androstane receptor (CAR) activation was responsible for pyrene‐induced mouse hepatotoxicity in studies with CAR knockout (CAR KO) mice . However, the toxic effects of pyrene are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…6C). Likewise, mCAR-independent induction of CYP1A1 and/or CYP1A2 by pyrene and TCPOBOP was observed in both WT and CAR-KO mice [45, 46]. Whereas cell-based CYP1A1 luciferase reporter assays revealed that CITCO does not active AhR (Data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…The well characterized endogenous ligands of CAR include bilirubin, bile acids, and androstanes [129132]. Exogenous CAR activators include medications (such as phenobarbital), environmental pollutants (PCBs) and pesticides/pesticide metabolites (methoxychlor, dichlorodiphenyldichloroethylene — DDE), and pyrene [84,133135]. CAR ligands are species-specific which can be attributed to limited conservation of CAR’s ligand binding domain.…”
Section: Constitutive Androstane Receptormentioning
confidence: 99%